Antifeedant Activity of Benzopyrans from Melicope latifolia - Mulyadi Tanjung (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Two benzopyrans, evodionol (1), and evodion (2) were isolated from the stem bark of Melicope latifolia. The structure of both compounds was identified based on 1D and 2D NMR, UV, and IR spectroscopy. Antifeedant activity of compounds 1-2, and ethyl acetate extract, showing inhibition value of 28.9; 31.3, and 46.8%, respectively, which were categorized as moderate.